Gut virome of mammals and birds reveals high genetic diversity of the family Microviridae. Issue 1 (8th June 2019) - Wang, Hao; Ling, Yu; Shan, Tongling; Yang, Shixing; Xu, Hui; Deng, Xutao; Delwart, Eric; Zhang, Wen
Abstract: Nineteen families of phages infecting bacteria or archaea are currently recognized by the International Committee on Taxonomy of Viruses (ICTV). Of these, only two have single-stranded DNA genomes, namely Inoviridae and Microvirida e. The distribution, genetic characteristics, and ecological roles of Microviridae remain largely under explored. Here, using viral metagenomics, we investigate the intestinal virome from human and twenty-four species of animals, as well as freshwater samples, containing abundant sequence reads showing similarity to the Microviridae . Eight hundred and sixty complete or near complete Microviridae -related genomes were generated, showing high levels of co-infections and sequence divergence. Sequence comparison and phylogenetic analysis showed that the Microviridae subfamily Gokushovirinae was highly prevalent and that some strains may qualify as new subfamilies. This study significantly augments our knowledge of the genetic diversity, genome evolution, and distribution in animal species of members of the family Microviridae.